Strategi Pembiayaan Pendidikan Berbasis Filantropi Islam dalam Memberdayakan Anak Yatim di Yayasan Yatim Mandiri Surabaya - Siregar, Murtika Sari (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
In the world of education, problems with finance or financing are common. Among the increasingly expensive tuition fees so that the increase in dropout rates. Therefore, in reducing dropout rates, institutions can innovate in developing education funding. One solution in developing education funding is by way of philanthropic-based education financing.The purpose of this study is to describe, strategy, implementation and implications in developing philanthropic-based financing. This study uses a qualitative approach to the type of case study research. The research location was in the Amphat National Amil Zakat Institute, Surabaya.To achieve the above objectives, a qualitative research approach is used with the type of case study research. Data collection techniques by: (1) Interview, (2) Observation, and (3) Documentation. To check the validity of the data using an extension of participation, perseverance of observation, and triangulation of data.Research findings show that (1) Islamic Philanthropy-Based Education Financing Strategies: (a) Freeing the cost of education for orphans, (b) Equitable education starting from the lower, middle to upper classes, (c) As school income. (2) Sources of funding in every Surabaya Independent Orphan education program are channeled in the form of scholarships and budgeting for the Orphan Mandiri educational institutions themselves, such as the Insik Cedikia Mandiri Boarding School (ICMBS), An-Najah Indonesia Mandiri Islamic High School (STAINIM) , Mandiri Entrepreneur Center (MEC) School.